PRODUKTIVITAS PEKERJA DALAM PEKERJAAN PEMASANGAN DINDING BATA DENGAN METODE CREW BALANCE CHART - Eddy Putra; Hendrik Sulistio (JMTS: Jurnal Mitra Teknik Sipil, 2020)
The determination of the magnitude of value of productivity is the first step that must be conducted to determine magnitude of increase productivity that can be applied in construction projects. The determination of value of productivity requires the completeness of data obtained from workers data collection. Data collection displayed in form of Crew Balance Chart to get unproductive time and coefficient of workers based on field conditions in the installation of brick and to increase the productivity of workers on construction project of Residential Houses Cempaka Baru. Methods of data collection using observations in the field, as well as the data processed by using simple math. From the results of the research known to time is unproductive time of workers on the job installation of brick wall construction projects Cempaka Baru on front area is 9,711%, and on back area is 48,737% so it can be called that workers in the front area is quite productive while the workers in back area tend to be not productive. The productivity of workers front area amounted to 0,98 m2/h while productivity in ideal conditions can reach 1,33 m2/h, while that for back area the productivity 1,53 m2/h while productivity ideally 2,25 m2/h.ABSTRAKPenentuan besarnya nilai produktivitas merupakan langkah awal yang harus dilakukan untuk mengetahui besarnya peningkatan produktivitas yang dapat diterapkan dalam proyek konstruksi. Penentuan nilai produktivitas memerlukan kelengkapan data yang didapat dari pendataan pekerja. Pendataan pekerja ini ditampilkan dalam bentuk diagram Crew Balance Chart untuk mendapatkan waktu tidak produktif dan koefisien pekerja berdasarkan kondisi lapangan dalam pekerjaan pemasangan dinding bata serta dapat meningkatan produktivitas pekerja pada proyek konstruksi Rumah Tinggal Cempaka Baru. Metode pengumpulan data dalam crew balance chart menggunakan observasi di lapangan, serta data diolah dengan menggunakan matematika sederhana. Dari hasil penelitian diketahui waktu tidak produktif pekerja pada pekerjaan pemasangan dinding bata proyek konstruksi Cempaka Baru pada area depan 9,711% dan pada area belakang 48,737% sehingga dapat dapat disebut pekerja pada area depan cukup produktif sementara pekerja pada area belakang cenderung tidak produktif. Produktivitas pekerja pada area depan sebesar 0,98 m2/jam sedangkan produktivitas dalam kondisi ideal dapat mencapai 1,33 m2/jam, sementara itu untuk area belakang produktivitasnya sebesar 1,53 m2/jam sedangkan produktivitas idealnya 2,25 m2/jam.